Malignant mastocytoma of a dog – a case report - Seiler, R. J.; Sheikh Omar, Abdul Rahman (Persatuan Doktor Veterinar Malaysia, 1979)
A malignant mastocytoma was seen in a female Doberman Pinscher dog. The primary tumor was surgically removed from the sub-cutaneous tissue over the right anterior mammary gland. Five weeks later the dog was moribund and necropsy revealed recurrence at the original site and metastases in regional lymph nodes and viscera. The neoplasm was characterised histologically by anaplastic mast cells, eosinophils and necrosis of collagen fibres and Grade 1malignancy was diagnosed.